Towards financial security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Towards Financial Self-Reliance. A Handbook on Resource Mobilization for Civil Society Organizations in the South. by R Holloway. Earthscan, with CIVICUS World Alliance for Citizen Participation and Aga Khan Foundation, 2001. 236 pp. ISBN 1 85383 773 3